Beryllium, tungsten and their alloys Be2W and Be12W: Surface defect energetics from density functional theory calculations. (August 2018) - Chen, L.; Sukuba, I.; Probst, M.; Kaiser, A.
Highlights: Surface energetics of beryllium–tungsten alloys depends strongly on the surface orientation and termination. Energetics is strongly correlated to the type, number, and distances of nearest neighbor atoms. Plane-wave density functional theory calculations of surface binding energies, adatom energies, and step edges. Tungsten atoms bind stronger on beryllium surfaces than vice versa. Abstract: The binding, adsorption and removal energies of atoms on the surfaces of Be with the major orientations (11 2 ¯ 0) and (11 2 ¯ 1), and of W and Be/W alloys with (110) and (111) orientations have been obtained from density functional theory calculations. An analysis of adatom formation on viable surfaces and of adsorption and step formation processes is provided as well. Possible surface changes at conditions occurring during plasma-wall interactions are discussed. The large differences of the energetic parameters for various surface orientations and terminations mean that atomistic modeling is indeed essential for understanding the behavior of PFMs in a fusion environment.